INVESTIGATING EFL TEACHERS’ PROFESSIONAL DEVELOPMENT IN FRATER DON BOSCO SENIOR HIGH SCHOOL LEWOLEBA - Wijaya, Kristian Florensio (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
Undoubtedly, to promote more holistic, pleasurable, and meaningful second language learning enterprises for learners, EFL teachers are advocated to sustainably hone their professional development concerning their knowledge and pedagogical competencies. This present qualitative study was conducted in the light of the critical incident technique to discover particular unforgettable teaching-learning events enabling teachers to promote significant changes in their vocation. Further, 10 self-reflective inquiries were also addressed to 2 invited senior EFL teachers working in Frater Don Bosco Senior High School Lewoleba, Nusa Tenggara Timur Province. Two major findings were revealed from these self-reflective inquiries namely EFL teacher’s sound desire to continue upgrading professional development through professional learning and EFL teacher’s strong intentions to improve learners’ target language competencies through the exhibition of professional development. Although the two invited EFL teachers had significantly fostered their professional development through profound caring, attentiveness, and understanding of learners’ distinctive learning backgrounds, it is indispensably required for Indonesian educational institutions to provide a considerable number of professional development training appropriate with varied teaching-learning contexts undergone by our teachers to ensure that a higher degree of professionalism resided within their careers and learners’ learning rides.